ALGORITHM VISUALIZATION IN TEACHING PRACTICE - Törley, Gábor (Acta Didactica Napocensia, 2014)
This paper presents the history of algorithm visualization (AV), highlighting teaching-methodology aspects. A combined, two-group pedagogical experiment will be presented as well, which measured the efficiency and the impact on the abstract thinking of AV. According to the results, students, who learned with AV, performed better in the experiment.